2004
DOI: 10.1021/es030650d
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Recovery of PCB-Contaminated Surface Sediments at the Sangamo-Weston/Twelvemile Creek/Lake Hartwell Superfund Site

Abstract: Natural recovery of contaminated sediments relies on burial of contaminated sediments with increasingly clean sediments over time (i.e., natural capping). Natural capping reduces the risk of resuspension of contaminated surface sediments, and it reduces the potential for contaminant transport into the food chain by limiting bioturbation of contaminated surface or near-surface sediments. This study evaluated the natural recovery of surface sediments contaminated with polychlorinated biphenyls (PCBs) at the Sang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 5 publications
2
50
2
Order By: Relevance
“…Biotic recovery trends observed in this study differ from the biotic trends reported at Lake Hartwell, where largemouth and hybrid bass have not measurably responded to decreases in surface sediment PCB concentrations (33). The time lag between surface sediment PCB concentrations and the response of indicator species at Lake Hartwell appears to be far greater than that observed at Saglek Bay.…”
Section: Resultscontrasting
confidence: 89%
“…Biotic recovery trends observed in this study differ from the biotic trends reported at Lake Hartwell, where largemouth and hybrid bass have not measurably responded to decreases in surface sediment PCB concentrations (33). The time lag between surface sediment PCB concentrations and the response of indicator species at Lake Hartwell appears to be far greater than that observed at Saglek Bay.…”
Section: Resultscontrasting
confidence: 89%
“…Natural deposition of clean material can result in contaminant concentrations that approach or achieve cleanup levels and reduce risks to human health and the environment Brenner et al, , 2004.…”
Section: Physical Isolation Dispersion and Reduced Contaminant Expomentioning
confidence: 99%
“…In 1991, PCBs were undetected in the study area at detection limits ranging from 0.49 to 2.0 g/L and in 1992, PCBs were undetected at detection limits of 1.2 or 1.3 g/L AQUATOX assumes that all PCB in sediment is associated with the detritus, which was modeled in AQUATOX as organic matter. The initial PCB concentration of sedimented detritus in the lake was calculated from data reported by Brenner et al (2004): 2 mg PCB per kg dry sediment, divided by 0.03 kg total organic carbon (TOC) per kg dry sediment, divided by 1.9 (standard AQUATOX conversion from TOC to organic matter) = 35 mg PCB/mg sediment organic matter. PCB load for inflow detritus was set based on yearly observed sediment concentrations at the sample site directly upstream of the USGS gage (Site SD002); the AQUATOX model conducts linear interpolation between the yearly values.…”
Section: Representation Of Pcbsmentioning
confidence: 99%
“…PCBs in sediments and aquatic fauna have been monitored since 1995 to gauge the effectiveness of Monitored Natural Recovery in lowering PCB concentrations in sediments and aquatic fauna (Georgia DNR, 2006). Brenner et al (2004) demonstrated that PCB concentrations in TCA sediments in 2001 and 2002 were in the range of 1 ppm, the recovery goal for sediments (U.S. EPA, 1994). The recovery goal for PCBs in fish tissue is 2.0 ppm, which is the current federally specified level for fish consumption (U.S. EPA, 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation